Providing care for older adults in the Emergency Department: expert clinical recommendations from the European Task Force on Geriatric Emergency Medicine - Lucke, J A; Mooijaart, S P; Heeren, P; Singler, K; McNamara, R; Gilbert, T; Nickel, C H; Castejon, S; Mitchell, A; Mezera, V; Van der Linden, L; Lim, S E; et al. (European geriatric medicine, 2022)
PURPOSE: Despite the rapidly expanding knowledge in the field of Geriatric Emergency Medicine in Europe, widespread implementation of change is still lacking. Many opportunities in everyday clinical care are missed to improve care for this susceptible and growing patient group. The aim was to develop expert clinical recommendations on Geriatric Emergency Medicine to be disseminated across Europe. METHODS: A group of multi-disciplinary experts in the field of Geriatric Emergency Medicine in Europe was assembled. Using a modified Delphi procedure, a prioritized list of topics related to Geriatric Emergency Medicine was created. Next, a multi-disciplinary group of nurses, geriatricians and emergency physicians performed a review of recent guidelines and literature to create recommendations. These recommendations were voted upon by a group of experts and placed on visually attractive posters. The expert group identified the following eight subject areas to develop expert recommendations on: Comprehensive Geriatric Assessment in the Emergency Department (ED), age/frailty adjusted risk stratification, delirium and cognitive impairment, medication reviews in the ED for older adults, family involvement, ED environment, silver trauma, end of life care in the acute setting. RESULTS: Eight posters with expert clinical recommendations on the most important topics in Geriatric Emergency Medicine are now available through https://posters.geriemeurope.eu/ . CONCLUSION: Expert clinical recommendations for Geriatric Emergency Medicine may help to improve care for older patients in the Emergency Department and are ready for dissemination across Europe.
Keywords: Emergency Medicine; Geriatrics; Acute care; Aged; geriatrie; Guidelines; urgentní lékařství; Humans; Frailty; Emergency Service, Hospital; křehkost; senioři; lidé; geriatrické hodnocení; Geriatric Assessment; Geriatric Emergency Medicine; urgentní služby nemocnice